Analysis of the Behaviour of Stone Column Stabilized Soft Ground Supporting Transport Infrastructure. (2016) - Basack, Sudip; Indraratna, Buddhima; Rujikiatkamjorn, Cholachat
Abstract: This paper presents an analytical and numerical study on the behavior of stone column stabilized soft ground supporting transport infrastructure. Analysis has been carried out on the response of reinforced soft ground under static and cyclic loadings relevant to transport corridors.